An Exploration of Teacher Resilience Related to the Merdeka Mengajar Platform (PMM) Program Based on Age and Work Experience Factors - Ketut Erika Sintya Dewi; Putu Nanci Riastini; Ni Wayan Eka Widiastini (Universitas Pendidikan Ganesha, 2026)
Elementary school teachers face various challenges in implementing the Merdeka Mengajar Platform (PMM) program, such as limited access to technology, insufficient technical training, and differences in adaptive abilities. These conditions require resilience so that teachers can adapt, remain productive, and support the success of the program. This study aims to describe the level of resilience of elementary school teachers in facing the PMM program in terms of age and work experience. The study employed a descriptive quantitative approach involving 33 elementary school teachers. The research instrument was a resilience questionnaire based on the seven dimensions proposed by Reivich and Shatté. The data were analyzed to identify trends in teachers’ resilience levels across different age groups and lengths of service. The results indicate that teachers demonstrate a high level of resilience, reflecting their adaptability, perseverance, and readiness to face PMM-based curriculum changes. Differences in resilience levels across age groups and work experience are not statistically significant; however, a pattern emerges showing that professional maturity and digital readiness contribute to variations in teachers’ adaptive capacities. These findings confirm that resilience is a key factor in the successful implementation of PMM and needs to be strengthened through continuous training, institutional support, and the development of technology-based professional competencies. This study implies that strengthening teacher resilience should be carried out systematically through continuous training programs, enhancement of digital literacy, and institutional support to ensure that the implementation of PMM can be more optimal and sustainable.